KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SEKOLAH (STUDI KASUS DI SMP SUSTER PONTIANAK) - Sudarti, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:This study aims to improve the quality of Sister Junior High School according to the principal leadership. This research is descriptive qualitative research. Data collection procedures are direct observation, in-depth interviews, and documentation. This discussion about: (1) in improving the quality of the school, the principal must have a planning or program that must be undertaken by all teachers based on their tasks and responsibility. (2) the quality of the school can increase if there is empowerment of teachers, administrative staff, and the students, the control of the principal to the tasks of each teacher, administrative staff, and learners, and the maximum evaluation of the program. (3) the program should be published or socialized so that it is supported and implemented by the teacher, administrative staff and student in accordance with their responsibilities. (4) commitment of teachers and students, the infrastructure areÂ  factors supporting the achievement of school quality and the factors that hamper the increase of school quality is less the function and role. Â  Keywords: Leadership, Principal, School Quality